Making blood transfusions safer - L Bordbar (Iran University of Medical Sciences, 1993)
Transfusion of blood products from an infected person with AIDS, is meant to infect recipient. Blood Products such as whole blood, red blood cells, platelets, plasma, frozen blood precipitate, factor VIII, factor IX, can be infected with HIV. Transmissions from blood factors can be seen in plasma from thousands of donors that were collected in a container and were used to treat hemophilia. Blood of an infected person can infect the entire volume of the product. Once the blood collection organizations realized the danger, they reacted to the issue and blood tests were performed on donors to separate contaminating agents